A Study of Slang in the Television Series Ginny & Georgia Season 1 Episode 1 - Ni Putu Whulan Gana Putri; Galuh Febri Putra; Ni Ketut Alit Ida Setianingsih (Pusat riset dan Inovasi Nasional, 2025)
This study explores the use of slang in the first episode of Season 1 of the television series Ginny & Georgia, focusing on identifying the types of slang employed by the characters and interpreting their meanings within conversational contexts. The research applies a descriptive qualitative approach, utilizing Allan and Burridge’s (2006) theory to categorize slang types and Leech’s (1981) theory of meaning to analyze their meanings. The analysis reveals five categories of slang: Fresh and Creative, Flippant, Imitative, Acronyms, and Clipping, with Flippant slang emerging as the most frequently used. Each slang term is examined for its contextual meaning, uncovering various types of meanings such as Conceptual, Connotative, Social, Affective, and Reflective Meanings. Based on the findings, Affective Meaning appears most prominently, reflecting the characters’ emotional tones and interpersonal dynamics. While some types of meanings like Collocative and Thematic Meaning were absent, the findings underscore how slang in the series operates beyond casual speech, serving as a linguistic tool to express identity, emotion, and cultural nuance.